2018
DOI: 10.3390/antiox7100130
|View full text |Cite
|
Sign up to set email alerts
|

Redox Signaling of NADPH Oxidases Regulates Oxidative Stress Responses, Immunity and Aging

Abstract: An accumulating body of evidence suggests that transient or physiological reactive oxygen species (ROS) generated by nicotinamide adenine dinucleotide phosphate (NADPH) oxidases act as a redox signal to re-establish homeostasis. The capacity to re-establish homeostasis progressively declines during aging but is maintained in long-lived animals to promote healthy aging. In the model organism Caenorhabditis elegans, ROS generated by dual oxidases (Duox) are important for extracellular matrix integrity, pathogen … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 105 publications
(198 reference statements)
3
36
0
Order By: Relevance
“…In line with this, antioxidants (including NAC that abrogates RIR), which have been proposed to protect against carcinogenesis, in fact foster lung carcinomas and metastasis (Breau et al, 2019;Le Gal et al, 2015;Wiel et al, 2019). More generally, defect in each of the players of the "Low-stress" response described here (NF-κB, PARP1, FOXO1, DUOX1 and DUOX2) share common phenotypes, such as defects in cell homeostasis and metabolism, ageing and cancer predisposition (Ewald, 2018;Tia et al, 2018;Tilstra et al, 2011;Vida et al, 2016;Little et al, 2017;Park & Hong, 2016;Pires et al, 2018). `…”
Section: Discussionsupporting
confidence: 53%
“…In line with this, antioxidants (including NAC that abrogates RIR), which have been proposed to protect against carcinogenesis, in fact foster lung carcinomas and metastasis (Breau et al, 2019;Le Gal et al, 2015;Wiel et al, 2019). More generally, defect in each of the players of the "Low-stress" response described here (NF-κB, PARP1, FOXO1, DUOX1 and DUOX2) share common phenotypes, such as defects in cell homeostasis and metabolism, ageing and cancer predisposition (Ewald, 2018;Tia et al, 2018;Tilstra et al, 2011;Vida et al, 2016;Little et al, 2017;Park & Hong, 2016;Pires et al, 2018). `…”
Section: Discussionsupporting
confidence: 53%
“…Among them, several lncRNAs as well as mRNAs were found to interact with REDOX-related mRNAs, i.e., duox and noxo1a (Fig 6-B). These two genes have been demonstrated to play important roles in response to oxidative stress (29,30). Also, our functional enrichment analysis indicated that both mRNAs were significantly enriched in the REDOX process, e.g., GO:0006979 (response to oxidative stress) and GO:0055114 (oxidation-reduction process).…”
Section: Network Analysis Reveals Lncrnas Implicated In Redox Regulationmentioning
confidence: 63%
“…Redox balance is thus critical to embryonic development. More importantly, ROS generated by nicotinamide adenine dinucleotide phosphate (NADPH) oxidases is a crucial redox signal to establish homeostasis (29). This knowledge directs us narrow down the huge number of mRNA-lncRNA interactions to a relatively small subnetwork exhibiting strong correlation to two REDOX-related genes, duox (NADPH oxidase) and noxo1a (NADPH oxidase organizer).…”
Section: Discussionmentioning
confidence: 99%
“…Under abnormal conditions of excessive activation, large amounts of ROS can be produced, resulting in oxidative stress damage (Carvalho and Moreira, 2018;Ewald, 2018;Montes et al, 2019). It has been reported that NOX, in particular, NOX2, is implicated in AD (González-Reyes et al, 2017;Jiang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%